Deficiency of laryngeal collagen type II in an infant with respiratory problems. Issue 6 (1st June 1998) - Frenzel, K; Amann, G; Lubec, B
Abstract : A dysmorphic infant is described who presented with laryngeal collapse leading to intubation and respiratory problems that were assigned clinically to the Sussman syndrome. The baby had repeated episodes of respiratory distress necessitating assisted ventilation. At 6 months old, uvulopharyngopalatotomy was done to enlarge the supraglottic airway without any benefit. Surgical reduction of the tongue and cricoid splitting did not ameliorate the respiratory distress; repeated extubation attempts failed with the baby developing stridor, respiratory distress, and episodes of cardiac arrest. At 10 months old he developed seizures and computed tomography showed diffuse cerebral atrophy consistent with hypoxic-ischaemic damage. He died at 17 months old. Western blots using antibodies against collagen α1 (II) showed an absence of collagen type II in laryngeal tissue, which may explain the laryngeal collapse and impaired respiratory functions.